Valuable Manifestations in Antara bin Shaddad,s Poetry (The Scientific Journal of University of Saba Region, 2022)
This research aims to study the moral values contained in Antara’s poetry, which are classified into three categories: the highest ideal ethics that are less present among members of societies, but Antara has this kind of ethics; realistic ethics that the majority of people have, and Antara already having them; ethics that Antara looked at and philosophized, and called at the following findings: first, the value theorizing in Antara’s poetry suggests that the Arab society before Islam reached a high level of maturity and awareness. Second, what we observe from the interconnection of the value system in Antara’s poetry may be due to the regularity of these values in his life, and its control over himself, and his identification with them. Third, Antara’s poetry also suggests that the highness of determination was the key to change in his life, the source of the transformation that took place in his personality, and the source of values and morals that were issued by him and adhered to them, and that he practiced this intentionally, and this gives him an additional distinction.
Keywords: Manifestations; Values; Ethics; Antarah ibn Shaddad